Cone-beam computed tomography evaluation of C-shape canals and longitudinal grooves of mandibular first and second molar teeth (Annals of Medical Research, 2021)
Aim: This study aims to evaluate the anatomical features and prevalence of C-shaped roots and longitudinal grooves in mandibular first and second permanent teeth using cone-beam computed tomography (CBCT).Material and Methods: CBCT records of first and second mandibular teeth from 839 patients who applied to the Department of Oral and Maxillofacial Radiology between 2011 and 2018 were used. The CBCT examination was performed at five different axial levels and the mandibular molars were classified as types of longitudinal groove and C-shape according to the Fan criteria. Differences between genders, age groups, left and right side and type of tooth were determined.Result: A total of 2903 teeth (1321 first molars and 1582 second molar) from 839 patients were included in the study. C-shaped canals were found in mandibular first molar teeth with a prevalence of 0.15%, while 4.1% in mandibular second molar teeth. Only two mandibular first molars exhibited C-shaped canal. Female patients had a higher prevalence than males. Longitudinal grooves were most commonly found lingual surface. Conclusions: The occurence of C-shaped canals in mandibular first and second molars among Turkish population was generally less than in other populations. CBCT is a valuable tool to evaluate the C-shaped root canal configuration in vivo. Keywords: Cone-beam computed tomography; C-shaped canal; mandibular molar
Keywords: Cone-beam computed tomography; C-shaped canal; mandibular molar